Surgical therapy versus observation for lamellar macular hole: a retrospective comparison study - Sanisoglu H (Dove Medical Press, 2013)
Huseyin Sanisoglu,1 Ahmet Elbay,2 Sahin Sevim,1 Ugur Celik,3 Fatma B Aktas,1 Ebubekir Durmus1 1Department of Ophthalmology, Haydarpasa Training and Research Hospital, 2Department of Ophthalmology, Pendik Government Hospital, 3Department of Ophthalmology, Beyoglu Eye Training and Research Hospital, Istanbul, Turkey Background: The purpose of this study was to compare anatomic and visual changes in patients with lamellar macular hole undergoing pars plana vitrectomy with those in patients undergoing follow-up only. Methods: In this retrospective consecutive case series study, we evaluated two groups of eyes, comprising 19 eyes from 19 patients with lamellar macular hole who underwent pars plana vitrectomy with internal limiting membrane peeling and 21 eyes from 21 patients with lamellar macular hole who had follow-up only. Corrected distance visual acuity (CDVA, in logMAR) and optical coherence tomography findings, including measurements of maximum diameter of lamellar defect and foveal thickness, and whether the inner segment/outer segment band was intact or not were documented at initial and follow-up examinations. Results: At initial examination, mean CDVA was 0.54 logMAR in the study group and 0.51 logMAR in the control group, and 0.33 logMAR and 0.55 logMAR, respectively, on final examination. In the study group, postoperative optical coherence tomography images were found to be normalized in ten patients (52.6%), improved in six (31.5%), unchanged in two (10.5%), and to have progressed to full-thickness macular hole in one (5.2%) in the intervention group, while all patients in the control group were found to have deteriorated within the follow-up period between March 2004 and June 2010. Conclusion: In patients with lamellar macular hole, combination treatment with pars plana vitrectomy and internal limiting membrane peeling appears to be effective, but further studies are required to establish new treatment modalities for patients who do not have a satisfactory outcome from treatment. Keywords: lamellar macular hole, pars plana vitrectomy, internal limiting membrane peeling, outcome